Google Docs: Enhancing Collaborative and Cooperative Learning in the 21st Century - Ooi Choon Meng (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
Teaching of writing has been an uphill task for teachers, as students find writing as the most difficult and boring task. Students are basically sitting quietly writing paragraphs after paragraphs on paper and hand it in at the end of the lesson. There is hardly any collaboration and cooperation among the students. Those who are weak in writing struggle to complete their work for there is barely any interaction or discussion among the peers.In the perspective of 21st century education, learning needs to be more interactive with teachers as facilitators, while students collaborate and cooperate in their writing task. Students are empowered to write creatively and effectively through collaboration and group discussion. This could be done via Google Documents, one of the apps which allows students to comment, edit, collaborate, share and view the revision history of learners work. Writing has taken a step further, as it is going paperless.This workshop introduces participants to 21st century teaching writing via Google Documents, which will help to enhance writing lessons.** Laptop and Internet connection are required.